SDF-1/CXCR4 Signaling Maintains Stemness Signature in Mouse Neural Stem/Progenitor Cells. (20th March 2017) - Ho, Shih-Yin; Ling, Thai-Yen; Lin, Hsing-Yu; Liou, Jeffrey Tsai-Jui; Liu, Fei-Chih; Chen, I-Chun; Lee, Sue-Wei; Hsu, Yu; Lai, Dar-Ming; Liou, Horng-Huei
Abstract : SDF-1 and its primary receptor, CXCR4, are highly expressed in the embryonic central nervous system (CNS) and play a crucial role in brain architecture. Loss of SDF-1/CXCR4 signaling causes abnormal development of neural stem/progenitor cells (NSCs/NPCs) in the cerebellum, hippocampus, and cortex. However, the mechanism of SDF-1/CXCR4 axis in NSCs/NPCs regulation remains unknown. In this study, we found that elimination of SDF-1/CXCR4 transduction caused NSCs/NPCs to lose their stemness characteristics and to encounter neurogenic differentiation. Moreover, Notch and RE1 silencing transcription factor (REST) both play an essential role in NSCs/NPCs maintenance and neuronal differentiation and were dramatically downregulated following SDF-1/CXCR4 cascade inhibition. Finally, we demonstrated that the expression of achaete-scute homolog 1 (Ascl1), a proneural gene, and p27, an antiproliferative gene, were significantly increased after genetic elimination of SDF-1 alleles. Our results support that the loss of functional SDF-1/CXCR4 signaling pathway in NSCs/NPCs induces exit of cell cycle and promotes premature neural differentiation.